Production and Utilization of Legumes Progress and Prospects - Hasanuzzaman, Mirza (IntechOpen, 2023)
This book contains nine comprehensive chapters addressing various aspects of legume crop biology, production, and utilization. The contributions summarize recent findings on legume crop prospects and problems, and their responses to the environment. Management of legume crops under a changing climate, as well as their food value, are also discussed. This book will be useful for undergraduate and graduate students, teachers, and researchers, particularly in the fields of agronomy, crop science, and food science.